THE PLACE OF FOLKLORISMS IN CHILDREN'S LITERATURE (Web of Teachers: Inderscience Research, 2025)
Folklorism is the process of influencing and using the traditions of folkloric art (folklore) on professional fiction, art or culture. Folklorism is not only a simple reproduction of folklore materials, but also their processing in a new artistic form, modern interpretation and incorporation into works of art. This article presents scientific ideas about the phenomenon of folklorism, the history of its origin, the influence of folklorism on written literature. As evidence of the ideas, scientific works on folklorism and the opinions of scientists are presented. Poems of children's poets are cited as examples. This article presents excerpts from the works of Anvar Obidjon, Gayratiy and Tolib Yuldosh. Through these excerpts, the poets' skill in using folklorism is revealed. Types of folklorism and considerations about them are given.